A direct energy reuse strategy for absorption air-conditioning system based on electrode regeneration method. (May 2021) - Yang, Junqin; Zhao, Hui; Li, Chenchen; Li, Xiuwei
Abstract: The absorption air-conditioning system is a good choice for green buildings. However, much energy waste in regeneration phase limits the performance of the traditional system. To solve this problem, an electrode regeneration method is proposed by using capacitive deionization (CDI) technology to concentrate absorbent solution. Another key advantage of electrode regeneration is the energy recovery characteristic, which further improves the performance of the absorption air-conditioning system. A complete energy recovery includes energy storage and energy reuse. Previous studies has analyzed energy storage efficiency (stored energy/input energy) in different conditions. However, these studies lack reports on energy reuse. Therefore, this paper presents a direct energy reuse strategy for an absorption air-conditioning system with two CDI stacks connected in parallel. The discharging efficiency (reused energy/stored energy) is investigated. The higher discharging efficiency is achieved with more discharging times and lower charging voltage. Combining energy storage and energy reuse, the higher total energy recovery efficiency (reused energy/input energy) is achieved with high charging voltage. The system performance system based on an electrode regeneration method is analyzed. Up to 44% of the stored energy could be recovered and the performance is doubled to 1.87 in contrast with no energy recovery. Highlights: A direct energy reuse strategy with two CDI stacks connected in parallel is constructed. Higher discharging efficiency is achieved with more discharging times and lower charging voltage.3 The higher total energy recovery efficiency is achieved with high charging voltage. Up to 44% of the energy stored in the absorbing CDI stack could be directly reused. Compared with no energy reuse, the performance of the system is doubled to 1.87.